Comparative study of ciprofol vs. propofol in carotid endarterectomy: focusing on mean arterial pressure, vasoactive drug use, and postoperative complications - Zheng, Xinxin; Deng, Shiyun; Tian, Lu; Zhang, Yanqing; Bai, Lin (Frontiers in Medicine, 2025)
AimThe aim of this study was to compare the effects of ciprofol and propofol on mean arterial pressure (MAP) management, vasoactive drug usage, and postoperative complications after carotid endarterectomy.MethodsA total of 103 patients were included in either the ciprofol (n = 50) or propofol (n = 53) group. The MAP was recorded at nine perioperative timepoints from before anesthesia (T0) to extubation (T8). We focused on the achievement rate of the target MAP during carotid cross-clamping at T4–T6. We also examined vasopressor use (norepinephrine, urapidil) and postoperative complications.ResultsIn terms of primary outcomes, the ciprofol group exhibited a higher MAP at T3 (before the skin incision; p = 0.006) and achieved the target MAP faster at T4–T5 (during carotid cross-clamping and 5 min after cross-clamping; p < 0.001) than did the propofol group. There were no statistically significant differences between the groups at T6 (10 min after cross-clamping; p = 0.360). The ciprofol group exhibited significantly better hemodynamic stability during extubation (p < 0.001). Regarding the secondary outcomes, the ciprofol group was administered a lower dosage of norepinephrine (p < 0.001) and had fewer cases of early cognitive dysfunction (eCD) (p = 0.024).ConclusionThese findings suggest that ciprofol offers advantages over propofol during carotid endarterectomy by optimizing MAP control, minimizing vasopressor use, and mitigating postoperative complications. Ciprofol may be the preferable anesthetic agent in carotid artery-related procedures.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2500104162.